Life Cycle Assessment and Circular Economy: A Case Study of a Photovoltaic Solar Panel in Brazil - Maceno, Marcell M. C.; Pilz, Tha ' isa L.; Oliveira, Daniel R. (Journal of Environmental Accounting and Management, 2026)
In Different from the linear economy, which traditionally considers any waste as garbage, the circular economy recognize waste as a valuable material potentially useful as a resource. This thinking is the main principle of the Circular Economy, a production model that attempts to counterbalance the traditional linear economy recommending a more sustainable model. Thus, we aim to evaluate the circularity, using Circular Economy Toolkit, Circular Economy Indicator Prototype, and Material Circularity Indicator and calculate the environmental impact through the Life Cycle Assessment (LCA) for a 1st Generation Photovoltaic Solar Panel (PSP) manufactured in Brazil. For applying the three CE tools and the LCA, the PSP composition was raised weighing the product parts. Besides this, we used a technical data sheet of the manufacturer to complement the data. In this context, a Brazilian scenario was elaborated in which all raw materials for the PSP assembly were virgin materials. For the PSP destination parts, 83% was recycled, and 17% was sent to landfills. The Circular Economy Toolkit results indicated a great potential for improvement in the preservation or repair, in the reform or remanufacturing, and in developing the product as a service. For the Circular Economy Indicator Prototype and Material Circularity Indicator, the circularity percentage obtained for each tool was 57.2% and 44.32%, respectively. Finally, the LCA has shown a positive environmental impact due to the generation of localized energy. This result is higher than the negative impact of the assembly and destination processes. In conclusion, LCA proved to be an essential technique to guide the actions toward a circular economy since the same product can simultaneously present excellent environmental performance results and a low degree of circularity.